OVERCOMING BARRIERS: A CONCEPTUAL FRAMEWORK ON POVERTY, DROPOUT, AND EDUCATIONAL INEQUALITY - Khofifah, Nurul; Shammimi, Ros; Hanim, Nor (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
School dropout rates among students from low-income backgrounds continue to be a significant issue in education systems globally. Poverty restricts access to educational resources, exacerbates family instability, lowers academic performance, and reduces student motivation, leading to higher dropout rates (UNESCO, 2020). Most studies analyze these factors in isolation, neglecting the complex connections through which poverty impacts educational outcomes. This conceptual paper presents a comprehensive framework connecting economic hardship to school dropout rates, influenced by factors such as family stress, academic disengagement, and unfavourable school environments. It also examines moderating influences like government assistance programs and community initiatives that may alleviate the detrimental impacts of poverty. By integrating perspectives from ecological systems theory (Bronfenbrenner, 1979) and social reproduction theory (Bourdieu, 1973), this research provides an in-depth understanding of dropout challenges. The framework highlights crucial intervention opportunities for policymakers, educators, and social organizations aimed at enhancing school retention for disadvantaged students. Future research should empirically validate this framework across diverse socioeconomic and cultural settings to inform more effective educational policies. This paper contributes to theoretical insights in dropout research while offering practical strategies to combat educational inequality.